2023
DOI: 10.3390/s23063023
|View full text |Cite
|
Sign up to set email alerts
|

Effective Ransomware Detection Using Entropy Estimation of Files for Cloud Services

Abstract: A variety of data-based services such as cloud services and big data-based services have emerged in recent times. These services store data and derive the value of the data. The reliability and integrity of the data must be ensured. Unfortunately, attackers have taken valuable data as hostage for money in attacks called ransomware. It is difficult to recover original data from files in systems infected by ransomware because they are encrypted and cannot be accessed without keys. There are cloud services to bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The targeting strategy of ransomware has been another area of focus, as studies have found that ransomware often maps the user environment to identify files of value, paying attention to recent files history and important folders [19,20]. It has been observed that ransomware typically calculates the entropy of file names and contents to determine their authenticity, ignoring files that appear auto-generated, to maximize its impact [21,22].…”
Section: Ransomware Feature Studiesmentioning
confidence: 99%
“…The targeting strategy of ransomware has been another area of focus, as studies have found that ransomware often maps the user environment to identify files of value, paying attention to recent files history and important folders [19,20]. It has been observed that ransomware typically calculates the entropy of file names and contents to determine their authenticity, ignoring files that appear auto-generated, to maximize its impact [21,22].…”
Section: Ransomware Feature Studiesmentioning
confidence: 99%
“…[8] introduced strategies aimed at the pre-encryption activities of crypto-ransomware, showing the benefits of early, proactive detection. The study by [41] also underlined the effectiveness of estimating file entropy for early detection in cloud services, pointing out the importance of file analysis in these strategies. In addition, research on employing machine learning for the classification of Bitcoin transactions related to ransomware provides a significant boost to early detection methods, underscoring the importance of early interventions in the fight against ransomware [42].…”
Section: Introductionmentioning
confidence: 96%